Template-Directed Condensations between Acyl Units - Sun, Sengen (My University, 1994)
Glycoluril 1 acts as a bifunctional template, allowing efficient and repetitive
Claisen-type condensations between attached acyl units. Thus acetoacetyl
derivative 3 was prepared from 1 via 2. After conversion to the crotonate
derivative 4 (2 steps, β-carbonyl reduction and dehydration), a second cycle of
acylation and condensation gave crotonyl-transferred product 5. Repetition ofthe
sequence gave the 8-carbon derivative 6. Reduction of 4 with L-Selectride
afforded the butyryl derivative 7. allowing further acetylation and condensation
reactions leading towards long fatty acid chains. The product ratio from
condensation of the acetyl butyryl derivative of 1 is 4:1 in favour of deprotonation
of the acetyl group and transfer of the butyryl group. Reaction of 7 with lithium
benzyloxide gave recovered 1 and benzyl butyrate. Treatment of crotonyl acetyl
[diagram removed]
derivative 8 with L-Selectride produced only the acetyl transferred condensation
product 9. A similar regioselectivity was observed with L-Selectride reduction of
other α,β-unsaturated compounds (e.g., the acetyl acryloyl derivative). Results
of isotopic-labelling experiments support an intramolecular acyl transfer
mechanism for these condensations. This system mimics some of the features of polyketide and fatty acid synthases, allowing intramolecular acyl transfer and
repetitive additions of acetate units to make linear carbon chains while the
growing chain remains attached to the template. This is a potentially useful
method for the synthesis of some natural products and some useful organic
intermediates, such as putative oligoketide biosynthetic precursors.
Keywords: Chemistry; Chemistry